Pendampingan Kegiatan MTQ di TPA Al-Hidayah di Kecamatan 2X11 Enam Lingkung Kabupaten Padang Pariaman - Indah, Novita Juliana Sari; Kustati, Martin; Gusmirawati, Gusmirawati (Al-DYAS, 2024)
Religious festivals have always been an interesting thing in Indonesian society. Not only does it attract attention, but it also has many benefits for society, especially the younger generation. For example, religious festivals such as MTQ bring the younger generation closer to the Koran. This research aims to see how effective MTQ is in attracting students' interest in getting closer to the Koran as well as re-functioning the surau as an education center. This service method is Participatory Action Research (PAR) which is an approach whose process aims at learning which begins with planning, taking action or action, and evaluating the results of the action. The results of this research prove that this assistance is going well, this is indicated by the smoothness of the author's activities from the beginning to the end of the activity, and then there is an increase in the students' ability to read the Koran with recitations. Not only that, this activity was also successful in attracting students' motivation to study, where students were seen to be very enthusiastic and happy during the implementation. Furthermore, MTQ's aim to attract the interest of the younger generation in surau activities has shown positive results. This was obtained from the statement of the santri guardian who stated that little by little the children had started to be active at the surau again.